Labor market regulation and the cyclicality of involuntary part-time work - Theresa Markefke; Rebekka Müller-Rehm (Journal for Labour Market Research, 2024)
In times of economic crisis, many employers in liberal labor markets reduce their employees' working hours, which leads to an increase in the incidence of involuntary part-time work. We analyze the effectiveness of working time regulation in preventing such an increase during downswings. For this we look at the case of Germany, where hours adjustments are highly restricted by law. Using a state-level panel regression approach, we find that the incidence of involuntary part-time work is positively associated with the unemployment rate but that the association is much weaker than in the US and in the UK. Transition probabilities between employment states over the cycle suggest two particular underlying mechanisms: First, already employed workers are more likely to want a full-time position in economic downturns ("added hours effect"). Second, job seekers make concessions with regards to their desired hours when labor market conditions are bad ("reservation hours effect"). We are the first to document these margins of cyclical hours adjustments which are fundamentally different from those in less regulated labor markets, where the cyclicality of involuntary part-time work is predominantly driven by hours changes at the same employer.
Keywords: E24; J23; J22; J21; 330; Business cycle; Hours adjustment; Involuntary part-time work; Labor market institutions